Yasmin Induced Pulmonary Embolism: a Case Report - Zhu Xiangjun; Chen Yin; Yang Yuehua; Sun Zhiming (Journal of Advanced Pharmaceutical Science And Technology, 2021)
We evaluate a case report of Yasmin induced pulmonary embolism in order to provide reference for safety use of oral contraceptives.
Keywords: Yasmin